Tacrina análogos: síntese, derivatização, bioatividade e fotofísica de sistemas heterocíclicos híbridos - Kappenberg, Yúri Giovane (2023)
This thesis presents the results related to the synthesis, structural characterization and evaluation of the in vitro enzymatic inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) of novel series of heterocycle hybrids analogous to 9-amino-1,2,3,4-tetrahydroacridine (Tacrine -THA), which contains thiophenes, 1,2,3-triazoles, isoxazoles, pyrroles and spiro-chromenes as structural modifiers and aimed at generating possible prodrugs in the treatment of Alzheimer's disease (AD). This work also presents a study of N-derivatization aiming the insertion of pyrroles, via Clauson-Kaas reaction, in order to investigate photophysical properties of interest (absorption and emission). Thus, three hybrid series were initially obtained, conjugating different five-membered heterocycles (thienopyridinamines, isoxazolopyridinamines and [1,2,3]triazolopyridinamines) to THA. For this purpose, heteroaryl-2-aminocarbonitriles (thiophene-, isoxazole- and 1,2,3-triazole-derivatives), simple cycloalkanones (cyclopentanone, cyclohexanone, cycloheptanone and 1-tetralone) and more complex ones (spiro[chroman-2,1 '-cycloalkan]-4-ones) were applied as building blocks. Thus, 34 (thirty-four) heterocycles analogous to THA were isolated and characterized in yields ranging to 4% - 88%, depending on the precursor carbonitriles, through methodologies that used AlCl3 as catalyst, in the absence or presence of solvent, under conventional thermal heating or by microwave irradiation. In sequence, the three new series of tacrine analogues (thiophene-, isoxazole- and 1,2,3-triazole-hybrids) were evaluated for their in vitro AChE and BChE inhibition activity. The experimental results of enzymatic inhibition were added to complementary studies of molecular docking and showed that all the developed compounds demonstrated better anti-ChE properties promising for the inhibition of BChE, possibly due to the size that the AChE active site has, being smaller than the of BChE, which could explain because the compounds are better inhibitors of BChE than AChE. In addition, N-derivatization reactions, enabling the construction of derivative pyrroles, via the Clauson-Kaas reaction, were applied to the modified thiophene-tacrines, leading to the obtainment of 12 (twelve) novel pyrroles in yields of 66% - 95%. These pyrrole derivatives had their photophysical properties investigated (absorption and emission) in solution (CHCl3). As a result, it was found that these pyrroles were the transition bands were observed in the ultraviolet region, with two main maximum absorption bands (280 and 350 nm), and exhibit fluorescence in solution (380-400 nm) and lifetime decay values of fluorescence (1.49-2.60 ns) are directly related and dependent on the substituents directly linked to the thiophene moiety of the compounds. All chemical compounds related to the novel series produced in this thesis were characterized by melting point and structurally elucidated via routine spectroscopic and spectrometric techniques, such as uni- (1H and 13C) and two-dimensional (HSQC and HMBC) NMR in solution, HRMS and single crystal X-ray diffraction.